Color-Coded Map Overlay Augmentation for Unmanned Vehicle Sensor Management. (December 2020) - Ehrenstrom, Jacob; Calhoun, Gloria; Frost, Elizabeth; Bartik, Jessica; Lee Van Abel, Anna; Behymer, Kyle; Ruff, Heath
Four color-coded overlays that augment a tactical map were evaluated as candidates for multi-unmanned vehicle (UV) sensor management by a single operator. Each overlay provided six levels of temporal information to indicate how long ago each map location had been viewed by a UV. Twelve participants completed 140 trials, each trial posing a question to be answered by retrieving spatial-temporal information from static map overlays. The accuracy of the participants' answers significantly differed as a function of overlay type. Suggestions for overlay design and future research methodology are provided.